1989
DOI: 10.1007/bf00001405
|View full text |Cite
|
Sign up to set email alerts
|

Home range, movements, and density of the central stoneroller, Campostoma anomalum, in a small Ohio stream

Abstract: SynopsisA population of central stonerollers, Campostoma anomalum, in Harker's Run, Butler County, Ohio U.S.A., was examined during autumn, 1980, to determine the species' movements, density, and home range size. During the study period, 170 fish were marked by fin clips and released into the specific pool or riffle where they were captured within the 187 m study section. Eighty percent of the recaptured, marked fish (20) were recaptured in their initial capture area (specific pool or riffle). No fish moved mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…The species is a widely distributed minnow native to eastern North America where it can often dominate stream communities in both numbers and biomass. As a bottom-feeding herbivore with a home range on the order of 35 m (±14 m) of stream length (Mundahl and Ingersol 1989), C. anomalum can exert strong direct and indirect effects on stream biota via top-down controls on filamentous algae and diatoms (Power et al 1985). The species favors algae-rich streams with high water quality, but stonerollers are moderately tolerant to pollutants and can therefore be found in a wide range of degraded or modified habitats (Waits et al 2008 We based all estimates of genetic diversity and divergence on cumulative analysis of C. anomalum collected from 2000 to 2003 (Waits et al 2008).…”
Section: Site Selection and Specimen Collectionsmentioning
confidence: 99%
“…The species is a widely distributed minnow native to eastern North America where it can often dominate stream communities in both numbers and biomass. As a bottom-feeding herbivore with a home range on the order of 35 m (±14 m) of stream length (Mundahl and Ingersol 1989), C. anomalum can exert strong direct and indirect effects on stream biota via top-down controls on filamentous algae and diatoms (Power et al 1985). The species favors algae-rich streams with high water quality, but stonerollers are moderately tolerant to pollutants and can therefore be found in a wide range of degraded or modified habitats (Waits et al 2008 We based all estimates of genetic diversity and divergence on cumulative analysis of C. anomalum collected from 2000 to 2003 (Waits et al 2008).…”
Section: Site Selection and Specimen Collectionsmentioning
confidence: 99%
“…In reviewing the methods of several movement studies, we discovered that this practice is not common. Typically, marked individuals are released immediately after being handled (e.g., Hill and Grossman 1987;Mundahl and Ingersoll 1989;Gatz and Adams 1994). While this approach may be acceptable in many situations (see Gowan and Fausch 1996), a recent study by Nordwall (1999) showed that electrofishing significantly increased the mobility of brown trout (Salvo truttu), especially within 24 h of handling (F. Nordwall, Department of Aquaculture, Swedish University of Agricultural Sciences, S-901 83 UmeB, Sweden, persona1 communication).…”
Section: Experimental Designmentioning
confidence: 99%
“…For example, in an 18 month study, Hill and Grossman (1987) estimated that the home range size of three small warmwater fish species was less than 20 m. Specific home range estimates for smallmouth bass and longear sunfish are slightly higher, ranging from 30 to 100 m (Gerking 1953;Berra and Gunning 1972). Mundahl and Ingersoll (1989) estimated that central stoneroller moved an average of only 35 m in 1 month.…”
Section: General Patterns Of Movementmentioning
confidence: 99%
“…For example, in an 18 month study, Hill and Grossman (1987) estimated that the home range size of three small warmwater fish species was less than 20 m. Specific home range estimates for smallmouth bass and longear sunfish are slightly higher, ranging from 30 to 100 m (Gerking 1953;Berra and Gunning 1972). Mundahl and Ingersoll (1989) estimated that central stoneroller moved an average of only 35 m in 1 month. Although we cannot estimate maximum movement distances for our marked fish, our results do not support the long-held view of restricted fish movement first proposed by Gerking (1953Gerking ( , 1959.…”
Section: General Patterns Of Movementmentioning
confidence: 99%